Haul-out pattern of itinerant male Antarctic fur seals (Arctocephalus gazella) at Laurie Island, South Orkney Islands - Carlini, Alejandro R.; Daneri, Gustavo A.; Casaux, Ricardo; Márquez, Marìa E. I. (Polar research, 2006)
The seasonal haul-out pattern of itinerant male Antarctic fur seals (Arctocephalus gazella) was determined by regular counts at Mossman Peninsula, Laurie Island, South Orkney Islands, from 1996 to 2005. Small numbers of animals began to arrive at the beach in late December / early January (mean date 28 December ± 15 days, n = 10). Peak numbers of animals ashore changed considerably between seasons. In 1996, 1998 and 2001, peak numbers were registered in March (6/3, 18/3 and 6/3, respectively). Numbers peaked in 1997, 1999 and 2005 at the end of January / beginning of February (26/1, 2/2 and 28/1, respectively). In 2000, 2002, 2003 and 2004 peaks were registered in the third week of February (15/2, 22/2, 14/2 and 20/2, respectively). Peaks in numbers of seals ashore also varied between years, being minimum during 2001 (2531 individuals) and maximum during 2006 (16 610 individuals). In March 1998 the coasts of Laurie Island were surveyed by navigating inflatable boats near the shoreline; 18 haul-out places were identified. The big differences in peak numbers, as well as in the dates of peak events among years, suggest that local conditions could have an effect on the numbers of animals hauled out in a given year. It may therefore be difficult to predict trends from summer censuses in non-breeding places.